Agir Flash : bulletin d'informations du Collectif homosexuel mixte Agir. (Paris : Agir, 1989)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijksRedactie : 42 rue d'Avron, 75020 Paris
Frans
Periodiek